Inpatient multimodal occupational rehabilitation reduces sickness absence among individuals with musculoskeletal and common mental health disorders: a randomized clinical trial - Gismervik, Sigmund Ø; Aasdahl, Lene; Vasseljen, Ottar; Fors, Egil A.; Rise, Marit B.; Johnsen, Roar; Hara, Karen; Jacobsen, Henrik B.; Pape, Kristine; Fleten, Nils; Jensen, Chris; Fimland, Marius S. (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'This study aimed to investigate whether inpatient multimodal occupational rehabilitation (I-MORE) reduces sickness absence (SA) more than outpatient acceptance and commitment therapy (O-ACT) among individuals with musculoskeletal and mental health disorders. ' ' METHODS ': 'Individuals on sick leave (2-12 months) due to musculoskeletal or common mental health disorders were randomized to I-MORE (N=86) or O-ACT (N=80). I-MORE lasted 3.5 weeks in which participants stayed at the rehabilitation center. I-MORE included ACT, physical exercise, work-related problem solving and creating a return to work plan. O-ACT consisted mainly of 6 weekly 2.5 hour group-ACT sessions. We assessed the primary outcome cumulative SA within 6 and 12 months with national registry-data. Secondary outcomes were time to sustainable return to work and self-reported health outcomes assessed by questionnaires. ' ' RESULTS ': 'SA did not differ between the interventions at 6 months, but after one year individuals in I-MORE had 32 fewer SA days compared to O-ACT (median 85 [interquartile range 33–149] versus 117 [interquartile range 59–189)], P=0.034). The hazard ratio for sustainable return to work was 1.9 (95% confidence interval 1.2–3.0) in favor of I-MORE. There were no clinically meaningful between-group differences in self-reported health outcomes. ' ' CONCLUSIONS ': 'Among individuals on long-term SA due to musculoskeletal and common mental health disorders, a 3.5-week I-MORE program reduced SA compared with 6 weekly sessions of O-ACT in the year after inclusion. Studies with longer follow-up and economic evaluations should be performed.
Keywords: cognitive behavioral therapy; fatigue; health services research; inpatient care; inpatient multimodal occupational rehabilitation; mental health; mental health disorder; musculoskeletal disease; musculoskeletal disorder; occupational rehabilitation; physical exercise; problem solving; psychiatry; randomized clinical trial; return to work; sickness absence